2015
DOI: 10.1002/mame.201500272
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Mediated Antibacterial Clay Nanocomposites: Exfoliation of Montmorillonite Nanolayers by IR825 Intercalation

Abstract: We report the exfoliation of montmorillonite (MMT) by IR825, a near infrared (NIR) active hyper‐thermal antibacterial nanocomposite, constructed using polyvinylpyrrolidione‐q‐catechol with sultones (C‐PVPS) through ionic exchange reactions. Studying this nanocomposite revealed a sharp increase in photothermal heat as a function of irradiation time, and the layered MMT structure is promising for optimizing the required thermal stability to increase the photothermal heat. Only 5 min of exposing an in vitro suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Antimicrobial phototherapies, such as photothermal and photodynamic therapies, have attracted considerable attention in treating of infected wounds due to their targeted selectivity, non-invasiveness, remote controllability and biological safety. [199][200][201] When the photothermal wound dressing is irradiated by NIR light, PTT kills microorganisms by raising the local temperature (450 1C) and causing physical damage (thermal damage) to bacteria. 202 These photothermal materials (including photosensitizer and metal materials) exhibit excellent mechanical, stable photothermal and electronic properties, so they have been extensively studied in tissue engineering research in recent years.…”
Section: Antibacterial Phototherapy Chitosan Hydrogelmentioning
confidence: 99%
“…Antimicrobial phototherapies, such as photothermal and photodynamic therapies, have attracted considerable attention in treating of infected wounds due to their targeted selectivity, non-invasiveness, remote controllability and biological safety. [199][200][201] When the photothermal wound dressing is irradiated by NIR light, PTT kills microorganisms by raising the local temperature (450 1C) and causing physical damage (thermal damage) to bacteria. 202 These photothermal materials (including photosensitizer and metal materials) exhibit excellent mechanical, stable photothermal and electronic properties, so they have been extensively studied in tissue engineering research in recent years.…”
Section: Antibacterial Phototherapy Chitosan Hydrogelmentioning
confidence: 99%
“…However, the short half-life (t1/2) of NO and bioactivities in other tissues have limited its profound therapeutic implications. In this context, CDs with photoresponsive 4-nitro-3-(trifluoromethyl) aniline attached have shown phototriggered NO release inside the cancer cells [144].…”
Section: In Vivo Studymentioning
confidence: 99%
“…11 In recent years, clays such as montmorillonites, bentonites, and smectites have been found to have antimicrobial properties which significantly reduce Gram-negative and Gram-positive bacterial growth. 14,15 Some studies have also revealed that nanocomposite-based polymer and organically modified clays can improve antimicrobial activities and reduce the biodegradability of polymers. 12,16 Thermoplastic polyurethane (TPU) has emerged as the most promising biopolymer candidate for devices requiring long-term implantation.…”
Section: Introductionmentioning
confidence: 99%